(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص: كثيرا ما تناول الدارسون مفهوم الحدث بمفهوم المحور العام أو القصة التي تعالجها الرواية، فإذا كان الحدث في الرواية الكلاسيكية يأخذ سمته التاريخية والواقعية، ولئن كان يتميز أيضا بالتسلسل المنطقي لطبيعة الأشياء، وتتابع الأحداث وتعاقبها، فإنه في الرواية المعاصرة من صنع القارئ، لأنه هو الذي يتجشم عناء إعادة ترتيب الأحداث المفككةِ البناءِ والترابط، وقد أجمع معظم النقاد أن الأحداث تستسقى، من الخبرات الإنسانية والتجارب الحياتية المختلفة، والمآسي التي تمر بها الأمم والمجتمعات. ونتيجة لما تزخر به الأمة الجزائرية من وقائع؛ وما حفلت به أوضاعها من أحداث متنوعة وتجارب متعددة ومحن مرت بها، فإن العنف/الموت والوطن يشكّلان ثنائية متميزة، ويعدّان من أهم المحاور التي تمثّل أساسيات تشكيل الخطاب الروائي عند الكتّاب الجزائريين، وإن كانت هناك محاور أخرى، تشكّل الحدث في الرواية الجزائرية المعاصرة، من حب ورمز وأسطورة، فكيف قرأ النقد الجزائري هذه الأحداث؟ كلمات دالة: الحدث، الرواية الجزائرية المعاصرة، العنف، النقد الجزائري. Abstract Scholars often dealt with the concept of the event in terms of the general theme or the story that the novel deals with. So, if the event in the classic novel takes its historical and realistic attributes, while it is also distinguished by the logical serialization of the nature of things, the succession and sequence of events, in the contemporary novel, it is made by the reader, because he is the one who bears the troubleof rearranging the disassembled and disconnected events. In fact, most critics have unanimously agreed that events are derived from human experiences, different life experiments, and the tragedies experienced/undergone by nations and societies.As a result of the Algerian nation’s richness and the various events, experiences, and tribulations/ordealsit has gone through, violence / death and the homeland constitute a distinct duality, and are considered among the most important axes that represent the basics of shaping the Algerian writers’ narrative discourse. And if there are other axes, it is the event, in the contemporary Algerian novel, of love, symbol and legend. Keywords: The violent event, contemporary Algerian novel, Algerian criticism